Mengoptimalkan Pengembangan Desa Wisata Jeruk Manis melalui Pembuatan Tourist Information dan Fasilitas Changing Room - Nova Salsabilla; Baiq Neny Rafika Apriliya; Wahyu Aprianto; Retsatina Widiawati; Aisyah Febrianti; Masayu Farah Rachmadani; Sanisa Septianingsih; Faizah Faizah; Nuryadin Ibnu Mas’ud; Muhammad Thoriq (Lembaga Pengembangan Kinerja Dosen, 2024)
Jeruk Manis Village is a village resulting from the expansion of Kembang Kuning Village, after its expansion Jeruk Manis established itself with new branding as a tourist village that is already known for its natural beauty and green rice fields that refresh the eyes. In its efforts to build a tourist village that promises visitors, Jeruk Manis has not provided adequate facilities such as the lack of tourist information for visitors, as well as inadequate changing rooms in several tourist attractions. Therefore, the purpose of KKN PMD University of Mataram for the July-August 2024 period is to optimize tourism in Jeruk Manis Village through making Tourist Information and improving Changing Room facilities. The implementation method used is field survey, location planning, design or design, and program implementation (production and promotion). The results obtained from the making of Tourist Information and Changing Room improvements have a stronger impact on the progress of the branding of the Jeruk Manis Tourism Village, with Tourist Information being a reference for foreign visitors when visiting Jeruk Manis Village. In addition, the placement of the Changing Room made of bamboo which adds to the attractiveness also ensures the comfort of visitors.